Eyewitnesses in the courtroom: a jury-level experimental examination of the impact of the Henderson instructions - Bergold, Amanda N. (Journal of experimental criminology, 2021)
The New Jersey Supreme Court in New Jersey v. Henderson (2011) proposed judicial instructions designed to assist juries in evaluating eyewitness evidence. The current work examines the impact of the Henderson instructions on deliberating jurors, and whether the jury deliberation process helps jurors use the Henderson instructions to evaluate eyewitness evidence., Seventy-nine juries composed of five to nine jurors each viewed a re-enacted criminal attempted rape trial in which the quality of the eyewitness variables (both system and estimator variables) and the presence of judicial instructions were manipulated., The Henderson instructions did not impact the deliberating jurors’ verdicts or the jury verdicts. Juries displayed sensitivity to the quality of system variables (e.g., unbiased instructions), rendering more guilty verdicts when the quality of system variables was good, and more acquittals when the quality of system variables was poor. For estimator variables (e.g., presence of a weapon), the observed pattern was in the opposite direction. Jurors discussed both system and estimator variables during deliberations more often when their quality was poor., The results indicate the importance of examining jurors’ sensitivity to eyewitness evidence at the jury level, and that the Henderson instructions do not aide/improve jury deliberations in cases involving eyewitness evidence.